Pengaruh Return On Asset, Public Ownership, dan Loan To Deposit Ratio Terhadap Tobin’s Q Pada Perusahaan Perbankan BUMN - Vellati, Dhalia; Oktaviani, Marista (Improvement: Jurnal Manajemen dan Bisnis, 2024)
This paper examines the influence of Return On Assets (ROA), Public Ownership (PO), and Loan To Deposit Ratio (LDR) on Tobin's Q in state-owned banking companies listed on the Indonesia Stock Exchange for ten years from 2012 to 2021. The method used is Data collection methods use quantitative approach documentation techniques. The data processed is secondary data from annual reports and state-owned banking financial reports from the Indonesia Stock Exchange from 2012 to 2021. The sample was determined using purposive sampling of 4 companies in the 2012-2021 period. The data that has been collected is then tested using Multiple Linear Regression in SPSS25. The study results show that simultaneously it has a significant influence on Tobin's Q, partially the Return On Asset (ROA), Public Ownership (PO) variables have a significant positive influence on Tobin's Q while the Loan To Deposit Ratio (LDR) variable has a significant negative influence on Tobin's Q. Keywords: Return On Asset (ROA), Public Ownership (PO), Loan To Deposit Ratio (LDR) and Tobin’s Q Tulisan ini mengkaji tentang pengaruh Return On Asset (ROA), Public Ownership (PO), dan Loan To Deposit Ratio (LDR) terhadap Tobin’s Q pada perusahaan perbankan BUMN yang terdaftar di Bursa Efek Indonesia selama sepuluh tahun 2012 hingga 2021. Metode yang dipakai adalah metode pengumpulan data menggunakan teknik dokumentasi pendekatan kuantitatif. Data yang diolah data sekunder sumber laporan tahunan dan laporan keuangan perbankan BUMN dari Bursa Efek Indonesia tahun 2012 hingga 2021. Penentuan sampel dilakukan dengan purposive sampling sebanyak 4 perusahaan di periode 2012-2021. Data yang telah dikumpulkan kemudian dilakukan Uji Hipotesis menggunakan Regresi Linier Berganda pada SPSS25. Hasil Kajian menunjukkan bahwa secara simultan memiliki pengaruh signifikan terhadap Tobin’s Q, secara parsial variabel Return On Asset (ROA), Public Ownership (PO) memiliki pengaruh positif signikfikan terhadap Tobin’s Q sedangkan variabel Loan To Deposit Ratio (LDR) memiliki pengaruh negatif signikfikan terhadap Tobin’s Q. Kata Kunci: Return On Asset (ROA), Public Ownership (PO), Loan To Deposit Ratio (LDR) and Tobin’s Q